Decision‐making for older patients undergoing emergency laparotomy: defining patient and clinician values and priorities. (21st June 2020) - Law, J.; Welch, C.; Javanmard‐Emamghissi, H.; Clark, M.; Bisset, C. N.; O'Neil, P.; Moug, S. J.; ,
Abstract: Aim: There remains limited knowledge on what patients value and prioritize in their decision to undergo emergency laparotomy (ELap) and during their subsequent recovery. The aim of this study was to explore factors in decision‐making and to reach a consensus amongst patients on the 10 most important priorities in decision‐making in ELap. Methods: Patients aged over 65 years who had required an ELap decision within the preceding 12 months (regardless of management) were identified and invited to attend a modified Delphi process focus group. Results: A total of 20 participants attended: eight patients, four relatives and eight perioperative specialists. The perioperative specialists group defined 12 important factors for perioperative decision‐making. The patient group agreed that only six (50%) of these factors were important: independence, postoperative complications, readmission to hospital, requirement for stoma formation, delirium (including long‐term cognition) and presence of an advocate (such as a friend or family member). Open discussion refined multiple themes. Agreement was reached by patients and relatives about 10 factors that they valued as most important in their ELap patient journey: return to independence, realistic expectations, postoperative complications, what to expect postoperatively, readmission to hospital, nutrition, postoperative communication, stoma, follow‐up and delirium. Conclusion: Patients and clinicians have different values and priorities when discussing the risks and implications of undergoing ELap. Patients value quality of life outcomes, in particular, the formation of a stoma, returning to their own home and remaining independent. This work is the first to combine both perspectives to guide future ELap research outcomes.